Effect of different zootechnical additives on egg quality in two quail production phases - Lemos, M. de (2017)
To evaluate the quality of eggs of quails fed with different additives in two stages of the productive period, 360 quails were distributed in a completely randomized design in a split plot scheme in time (9 to 23 and 24 to 39 weeks of age) with five treatments and eight repetitions of nine birds each, organized as follows: control, antibiotic, prebiotic, probiotic, and symbiotic. The analyzed variables were: Haugh unit, yolk index, percentage of egg components, shell thickness measured by the micrometer and the SEM. The supply of additives in the second period increased Haugh units, and in both periods provided an increase in the percentage of yolk and shell and improved the thickness of the shell and its membranes. The inclusion of additives was more effective in promoting weight gain in eggs and the percentage of egg yolk and egg shell from 24 to 39 weeks of age. The shell thickness (SEM) improved after inclusion of antibiotic and symbiotic in feed in the second period. The addition of additives in food improved the quality of Japanese quail egg throughout the productive period. Antibiotics and symbiotics proved to be more effective in improving shell thickness of the eggs produced in the second productive period.